Derivation in a word-based morphology - Díaz Vera, Javier E. (Linguistica (Ljubljana), 2011)
In this paper I describe the process of grammaticalization of Old English causative verbs through the analysis of some of the different strategies for the expression of causation in three different lexical domains: PHYSICAL PERCEPTION, COGNITION and EMOTION. The etymological analysis of these verbs indicates that, in the case of the three lexical domains under scrutiny, causation was lexicalized and conceptualized as forced movement or change of an external (as in the case of verbs of FEELING; e.g. OE hieran 'to hear') or internal (i.e. verbs of COGNITION and some EMOTION verbs; e.g. OE gemynan 'to remember' and OE hiertan 'to encourage') part of the body.
Keywords: ancien anglais; anglais; angleščina; besedotvorje; English; formation des mots; glagol; izpeljanke; mots dérivés; stara angleščina; verb; verbe; word formation